Aerobic exercise training normalizes central blood pressure regulation after oral glucose loading in overweight/obese men. (2nd January 2019) - Yoshikawa, Toru; Kumagai, Hiroshi; Myoenzono, Kanae; Tsujimoto, Takehiko; Tanaka, Kiyoji; Maeda, Seiji
ABSTRACT: Central systolic blood pressure (cSBP) decreases after a meal or glucose challenge, but this response is impaired in obesity-related disorders. We investigated whether aerobic exercise training improves cSBP regulation during an oral glucose tolerance test (OGTT) in overweight/obese men. Thirteen overweight/obese men and six normal-weight men (as an alternative comparison instead of a no-exercise group) completed a 12-week aerobic exercise training program. Before and after the program, cSBP (i.e., radial second systolic pressure) was measured using an applanation tonometry at fasting and both 60 min and 120 min after 75 g glucose loading. Before and during the program, physical activity (PA) time was recorded using a tri-axial accelerometer. Pre-training, cSBP was significantly decreased with glucose loading in normal-weight men, while cSBP did not change in overweight/obese men. Post-training, a significant decrease in cSBP was observed in both groups following glucose loading. In addition, the increase in vigorous PA time during the exercise program was significantly correlated to the increase in area above the curve for cSBP during OGTT (demonstrating an improvement in the cSBP response to glucose loading) after the exercise program. These findings may provide novel insights into the role of PA in reducing the cardiovascular risk in obesity.